2016
DOI: 10.1021/acs.nanolett.6b00689
|View full text |Cite
|
Sign up to set email alerts
|

Nanotexturing To Enhance Photoluminescent Response of Atomically Thin Indium Selenide with Highly Tunable Band Gap

Abstract: Manipulating properties of matter at the nanoscale is the essence of nanotechnology, which has enabled the realization of quantum dots, nanotubes, metamaterials, and two-dimensional materials with tailored electronic and optical properties. Two-dimensional semiconductors have revealed promising perspectives in nanotechnology. However, the tunability of their physical properties is challenging for semiconductors studied until now. Here we show the ability of morphological manipulation strategies, such as nanote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
175
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(198 citation statements)
references
References 60 publications
20
175
0
Order By: Relevance
“…Among these vdW crystals, γ-InSe, a direct-band gap semiconductor, is attracting increasing interest. Strong quantum confinement effects with decreasing layer thickness and high room temperature electron mobility (>0.1 m 2 V −1 s −1 ) have been achieved in exfoliated InSe and/or films grown by physical vapour deposition [14][15][16][17][18][19]. Although the chemical stability of InSe has been questioned [20], recent research has shown that 2D InSe can be chemically inert under ambient conditions [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among these vdW crystals, γ-InSe, a direct-band gap semiconductor, is attracting increasing interest. Strong quantum confinement effects with decreasing layer thickness and high room temperature electron mobility (>0.1 m 2 V −1 s −1 ) have been achieved in exfoliated InSe and/or films grown by physical vapour deposition [14][15][16][17][18][19]. Although the chemical stability of InSe has been questioned [20], recent research has shown that 2D InSe can be chemically inert under ambient conditions [21].…”
Section: Introductionmentioning
confidence: 99%
“…InSe/hBN)13 and texturised (e.g. InSe/SiO 2 )18 layers. In the latter case, the surface of InSe flakes is bent by SiO 2 nanoparticles trapped between the flakes and the substrate, thus enhancing the optical emission due to increased light scattering and modified dipolar selection rules18.…”
mentioning
confidence: 99%
“…On the one hand, this issue is important for 2D semiconductors different from 2D TMDs [46]. In fact, the nature of the orbitals involved in the optical bandgap and the dipolar selection rules for optical transitions of 2D InSe -a semiconductor with a highly tunable band gap [35,51] -suggest that InSe could be an example of a 2D material with an important out-of-plane dipole contribution. On the other hand, the design of multilayer structures with optimized light extraction capabilities (independently of their dipole orientation) is also relevant for 2D TMDs, as it may allow to relax nearly flat requisites of devices based on these materials to provide an optimal response.…”
Section: Source Term Methods For the Design Of Multilayer Devices Withmentioning
confidence: 99%
“…However, this model assumes normal incidence of light for both excitation and emission, which limits its applicability for the design of devices in which the angular light emission pattern or the power distribution into guided and leaky modes becomes a relevant parameter. In addition to this, the normal emission approximation would be expected to fail to account for light emission patterns of active 2D materials with vertical emitting dipoles (as would be the case for 2D materials such as InSe [35,36]). In order to overcome such issues, it is possible to use matrix-based analytical models under the assumption of dipolar nature of optical processes taking place in semiconductors.…”
Section: Introductionmentioning
confidence: 99%